Nitrous oxide fluxes and nitrogen cycling along a pasture chronosequence in Central Amazonia, Brazil - B. Wick; E. Veldkamp; W. Z. de Mello; M. Keller; P. Crill (Biogeosciences, 2005)
We studied nitrous oxide (N2O) fluxes and soil nitrogen (N) cycling following forest conversion to pasture in the central Amazon near Santarém, Pará, Brazil. Two undisturbed forest sites and 27 pasture sites of 0.5 to 60 years were sampled once each during wet and dry seasons. In addition to soil-atmosphere fluxes of N2O we measured 27 soil chemical, soil microbiological and soil physical variables. Soil N2O fluxes were higher in the wet season than in the dry season. Fluxes of N2O from forest soils always exceeded fluxes from pasture soils and showed no consistent trend with pasture age. At our forest sites, nitrate was the dominant form of inorganic N both during wet and dry season. At our pasture sites nitrate generally dominated the inorganic N pools during the wet season and ammonium dominated during the dry season. Net mineralization and nitrification rates displayed large variations. During the dry season net immobilization of N was observed in some pastures. Compared to forest sites, young pasture sites (≤2 years) had low microbial biomass N and protease activities. Protease activity and microbial biomass N peaked in pastures of intermediate age (4 to 8 years) followed by consistently lower values in older pasture (10 to 60 years). The C/N ratio of litter was low at the forest sites (~25) and rapidly increased with pasture age reaching values of 60-70 at pastures of 15 years and older. Nitrous oxide emissions at our sites were controlled by C and N availability and soil aeration. Fluxes of N2O were negatively correlated to leaf litter C/N ratio, NH4+-N and the ratio of NO3--N to the sum of NO3--N + NH4+-N (indicators of N availability), and methane fluxes and bulk density (indicators of soil aeration status) during the wet season. During the dry season fluxes of N2O were positively correlated to microbial biomass N, β-glucosidase activity, total inorganic N stocks and NH4+-N. In our study region, pastures of all age emitted less N2O than old-growth forests, because of a progressive decline in N availability with pasture age combined with strongly anaerobic conditions in some pastures during the wet season.